Efficacy of eccentric exercise in lower limb tendinopathies in athletes - Frizziero, A.; Vittadini, F.; Fusco, A.; Giombini, A.; Masiero, S. (The Journal of Sports Medicine and Physical Fitness, 2016)
Tendinopathies are among the most frequent sport injuries, therefore their correct treatment is a crucial issue in sports medicine practice. In most of the cases, these multifactorial conditions are related to overuse and characterized by activity-induced pain, local tenderness and swelling. Although tendinopathies are common, their treatment is not easy. Currently, it is generally accepted that their management should include early functional exercises. Eccentric exercise (EE) is considered a fundamental therapeutic resource, especially for the treatment of Achilles and patellar tendinopathies. This article focuses on the use of EE for the treatment and prevention of the lower limb tendinopathies, evaluates the existing programs and their efficacy, and reviews the possible mechanisms of the healing process and the action of EE on tendon structure. EE-based treatments are useful to improve symptoms and function in lower limb tendinopathies, but more evidence is still required to devise an adequate dose-response model and to determine their long-term effects.